PALEMBANG CITY TOUR GUIDE APPLICATION WITH SHORTEST ROUTE SEARCH USING A* METHOD - Naris Kirana; Aryanti; Sarjana (RADJA PUBLIKA, 2025)
In the current digital era, technology has become an essential tool in planning travel experiences. Tourists often face challenges in determining efficient travel routes amidst the numerous available tourist attractions. A map-based application that provides recommendations for the shortest routes can help optimize tourists' time and experience. Palembang, as a tourist destination rich in history and culture, faces challenges in accommodating first-time visitors, particularly in finding efficient travel routes. To address this issue, the development of a tourist guide application based on mapping technology and route-search algorithms, such as the A* method, can serve as an effective solution. This application can offer guidance on the fastest and shortest routes, avoid traffic congestion, and enhance the overall tourist experience. Furthermore, it supports the tourism sector by promoting local attractions and making it easier for tourists to plan their trips. By implementing this technology, the quality of the tourism experience in Palembang can be improved, in line with the global trend of digitalization in the tourism industry.